Kindergarten Teachers' Responses to Career Parents Seen from the Social Emotional Aspects of Children Aged 5-6 Years - Habibah, Anna; Pranoto, Yuli Kurniawati Sugiyo (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
This study aims to investigate the response of kindergarten teachers to career parents from the social-emotional perspective of 5-6 year old children. The respondents to the study were six kindergarten teachers in Semarang City. The research method used in the study is a type of qualitative approach with a case study research design, data collection using interview measurement instruments, observation and documentation. Data analysis was carried out by data reduction and triangulation to validate the research results. The results of the study show that career parents have an impact on children's social-emotional behavior. Positive Impact Children with career parents tend to be independent, adaptive, have good social interaction, and quickly adapt to a new environment. As a negative impact, children often experience a lack of affection, difficulty in managing emotions, and lack of self-regulation. The implications of this study include the need to increase cooperation between teachers and parents to create communication of children's needs, parents provide quality time and choose caregivers who are competent in the field of children, in order to optimize child development.